2013
DOI: 10.4172/2167-1168.1000205
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Primary Nursing Care Model: A Systematic Review

Abstract: Background: Nursing care models provide the infrastructure for organizing and delivering care to patients and families. Over the decades, different models have waxed and waned. Since the 1980s, the primary nursing model has gained increasing prominence. However, there is no systematic research evidence on the effects of this model for patients, their family members, nursing staff or the care organization. This subject has much current relevance because of the requirement to develop evidence-based nursing care.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 49 publications
1
28
0
1
Order By: Relevance
“…Although it is a patient-centered model and supports nurse professionalism and autonomy, nurses dislike the primary nursing system. 31 Nurses in this study reported their limited autonomy, which could explain why they dislike the primary nursing system. Nurses dislike the total patient care and team nursing systems.…”
Section: Associations Between the Organizational Characteristics Ofmentioning
confidence: 77%
“…Although it is a patient-centered model and supports nurse professionalism and autonomy, nurses dislike the primary nursing system. 31 Nurses in this study reported their limited autonomy, which could explain why they dislike the primary nursing system. Nurses dislike the total patient care and team nursing systems.…”
Section: Associations Between the Organizational Characteristics Ofmentioning
confidence: 77%
“…Models of care delivery, such as primary nursing, which allow nurses to engage in relationshipbased interactions with patients to plan and coordinate care over time, are considered essential to fight fragmentation and to achieve quality, person-centred nursing care (Manthey, 2003;Tiedeman & Lookinland, 2004). While primary nursing has been utilized in many different care settings around the globe over several decades, its research base remains relatively modest, with most studies published in the last century (Hoffmann Kusk & Groenkjaer, 2016;Mattila et al, 2014). Consequently, there is a need to extend research-based insights into the way primary nursing has been implemented in acute inpatient settings and to discern its association with quality of person-centred nursing care.…”
Section: Introductionmentioning
confidence: 99%
“…Primary nursing has been linked with quality and satisfaction with care, improved job satisfaction and reduced cost of care (Hoffmann Kusk & Groenkjaer, 2016;Hongwei, Senqi, Thobaben, Yanwen, & Tao, 2011;Mattila et al, 2014). For instance, research reports greater nurse understanding of patients, more concern and communication with families, increased information giving, greater considerations for discharge planning and higher contribution to overall positive hospitalization experience on units utilizing primary nursing versus control units or baseline (Frohlich, Becker, Handel, & Spirig, 2013;Sellick, Russell, & Beckmann, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations